Identification of bromelain subfamily proteases encoded in the pineapple genome - Ashley G. Yow; Hamed Bostan; Roberto Young; Giuseppe Valacchi; Nicholas Gillitt; Penelope Perkins-Veazie; Qiu-Yun (Jenny) Xiang; Massimo Iorizzo (Scientific Reports, 2023)
Abstract Papain (aka C1A) family proteases, including bromelain enzymes, are widespread across the plant kingdom and play critical regulatory functions in protein turnover during development. The proteolytic activity exhibited by papain family proteases has led to their increased usage for a wide range of cosmetic, therapeutic, and medicinal purposes. Bromelain enzymes, or bromelains in short, are members of the papain family that are specific to the bromeliad plant family. The only major commercial extraction source of bromelain is pineapple. The importance of C1A family and bromelain subfamily proteases in pineapple development and their increasing economic importance led several researchers to utilize available genomic resources to identify protease-encoding genes in the pineapple genome. To date, studies are lacking in screening bromelain genes for targeted use in applied science studies. In addition, the bromelain genes coding for the enzymes present in commercially available bromelain products have not been identified and their evolutionary origin has remained unclear. Here, using the newly developed MD2 v2 pineapple genome, we aimed to identify bromelain-encoding genes and elucidate their evolutionary origin. Orthologous and phylogenetic analyses of all papain-family proteases encoded in the pineapple genome revealed a single orthogroup (189) and phylogenetic clade (XIII) containing the bromelain subfamily. Duplication mode and synteny analyses provided insight into the origin and expansion of the bromelain subfamily in pineapple. Proteomic analysis identified four bromelain enzymes present in two commercially available bromelain products derived from pineapple stem, corresponding to products of four putative bromelain genes. Gene expression analysis using publicly available transcriptome data showed that 31 papain-family genes identified in this study were up-regulated in specific tissues, including stem, fruit, and floral tissues. Some of these genes had higher expression in earlier developmental stages of different tissues. Similar expression patterns were identified by RT-qPCR analysis with leaf, stem, and fruit. Our results provide a strong foundation for future applicable studies on bromelain, such as transgenic approaches to increase bromelain content in pineapple, development of bromelain-producing bioreactors, and studies that aim to determine the medicinal and/or therapeutic viability of individual bromelain enzymes.